Populations of Erythrina velutina Willd. at risk of extinction - Melo, M. F. V. [UNESP]; Goncalves, L. O.; Rabbani, A. R. C.; Alvares-Carvalho, S. V.; Pinheiro, J. B.; Zucchi, M. I.; Silva-Mann, R. (Funpec-editora, 2015)
The goal of this study was to characterize the structure of two natural populations of the coral tree using RAPD and ISSR markers. The study evaluated all individuals in two different areas in the northeastern region of Brazil: the first was in the riparian area, 10 km x 100 m along the edge of the lower Sao Francisco River, and the second was in the municipality of Pinhao, in a semiarid region between the municipalities of Necpolis and Santana do Sao Francisco. We used all the coral trees present in those two areas (37 individuals). The results of the RAPD and ISSR markers were highly congruent, supporting the reliability of the techniques used. Similarity was estimated using the Jaccard arithmetic complement index. A dendrogram was constructed using the unweighted pair group method with arithmetic mean cluster algorithm, and the robustness of the data was bootstrapped with 5000 replicates. A principal coordinate analysis was performed on the basis of Jaccard coefficients. The total genetic variation observed was 21%, corresponding to the variation between the populations, and 79% of the variation was observed within the populations.
Keywords: RAPD; ISSR; Endangered species; Genetic variability; Molecular markers